Exposure to Abamectin affected early embryonic development and caused changes in erythrocytes in chicken embryos (Gallus gallus) - saad, kawakeb; Hamad, Bushra (Journal of Pure & Applied Sciences, 2025)
Early embryonic development is tightly regulated, and environmental factors can disrupt vital processes, resulting in poor embryo development. Abamectin, a pesticide and insecticide, has been shown to cause infertility in farmers. Despite its benefits, little is known about its impact on embryonic development and pregnancy. Therefore, this study aimed to examine the effects of Abamectin at two different concentrations on the nuclear erythrocyte morphology and general embryonic development in domestic Gallus chick embryos. Eggs were injected with Abamectin (ABM) at doses of 0.01 mg/kg and 0.05 mg/kg body weight per egg at two stages of development: the zero and third days of incubation. The embryos were collected on the fifth and ninth days of incubation, and their morphology was examined under a dissecting microscope. Blood samples were collected on the twelfth day of incubation. Blood smears were prepared on slides and stained; the density of blood cells, as well as the shape and abnormalities of nuclei, were examined under a light microscope. The results from this study demonstrate that exposure to ABM led to developmental defects in embryos at stages HH29 to HH38. These defects affected overall morphology, blood vessel formation, and erythrocyte shape, with higher concentrations producing more severe outcomes.